Teachers’ Pedagogical Competence for Fostering Religious Moderation Awareness in the Digital Era: A Phenomenological Study of Madrasahs in East Java - Qoyyumillah, Nur Iffah; Aziz, Imam Nur (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
The Proliferation of radical content in the Digital world presents both challenges and opportunities for religious education. Teachers play a key role in guiding students to address this, but research on the specific pedagogical competencies needed to foster religious moderation in the classroom remains limited. This research investigated the role of teachers’ pedagogical competence in promoting awareness of Islamic moderation in madrasahs during the digital era. Data were collected through in-depth interviews, classroom observations, and document analysis of madrasah teachers in East Java, Indonesia using a qualitative approach with an interpretative phenomenological design. The research findings reveal that teachers’ pedagogical competence is manifested through three integrated dimensions: first, curriculum integration by embedding Islamic moderation values into learning materials; second, technological pedagogical mastery through the use of digital tools to facilitate critical discussions on religious issues; and third, management of inclusive learning environments and student character assessment that fosters dialogue and values differences. These findings serve as a framework for designing a Sustainable Professional Development (SPD) program. This program should not only focus on general digital literacy but specifically on enhancing teachers' ability to curate digital moderation-based content, manage sensitive online-offline dialogues, and integrate multi-layered pedagogical evaluations. For policymakers, these findings recommend integrating the principles of Religious Moderation into the core Curriculum of teacher training to prepare educators capable of responding to the dynamics of the Digital age.